Establecimiento y desarrollo de plántulas de Tabebuia rosea (Bignoniaceae) en una selva subcaducifolia manejada de la costa Pacífica de México - Mora Santacruz, Antonio (2006)
We evaluated the effect of soil “scarification” and vegetation clearing treatments on the natural regeneration and initial development of Tabebuia rosea (Bertold) DC. seedlings in a moderate sized semideciduous tropical forest subjected to wood harvesting on the coast of Jalisco, Mexico. The treatments were applied under “seed” trees, and the number of germinated seedlings and their development were evaluated for nine months. Soil “scarification” promoted seed germination and initial seedling development, while the control of the competing vegetation increased the seedling growth and reduced their mortality. These results should be taken into account for the natural regeneration of this species, after clearing, to improve wood production, and should be incorporated into the silvicultural techniques currently developed in the region.